Chryseobacterium oryzae sp. nov. and Chryseobacterium suipulveris sp. nov., isolated from Andong sikhye and pigpen dust, respectively. Issue 10 (6th October 2022) - Heo, Jun; Won, Miyoung; Lee, Daseul; Kim, Jeong-Seon; Han, Byeong-Hak; Kim, Soo-Jin; Hong, Seung-Beom; Kwon, Soon-Wo
Abstract : Two Gram-stain-negative, aerobic, mesophilic, rod-shaped bacteria, ADR-1 T and SC2-2 T, were isolated from Andong sikhye and dust in a pigpen, respectively. The phylogenetic tree on the basis of 16S rRNA gene sequences showed that strains ADR-1 T and SC2-2 T were members of the genus Chryseobacterium and revealed the highest sequence similarities to Chryseobacterium binzhouense LM2 T (97.6 %) and Chryseobacterium koreense Chj707 T (94.9 %), respectively. Phylogenomic treeing using 92 core genes clearly indicated that strain ADR-1 T clustered with Chryseobacterium echinoideorum CC-CZW010 T, Chryseobacterium binzhouense LM2 T and Chryseobacterium taihuense CGMCC 1.10941 T, and strain SC2-2 T formed a compact cluster with Chryseobacterium koreense CCUG 49689 T . The digital DNA–DNA hybridization (dDDH) and orthologous average nucleotide identity (ANI) values of strain ADR-1 T with the closely related species of the genus Chryseobacterium were ≤24.4 % and ≤80.7 %, and those of strain SC2-2 T were ≤24.0 % and ≤77.8 %, respectively, which are well below the cut-off values of species discrimination (>70 % dDDH and >95–96 % ANI). The only respiratory quinone in both strains was menaquinone 6. The polar lipid profile of strain ADR-1 T comprised phosphatidylethanolamine, four unidentified aminolipids and three unidentified lipids, while strain SC2-2 T contained phosphatidylethanolamine, two unidentified aminolipids, one unidentified aminophospholipid and five unidentified polar lipids. The major fatty acids (>10 %) of strain ADR-1 T were iso-C15 : 0, summed feature 9 (iso-C17 : 1  ω 9c and/or C16 : 0 10-methyl), iso-C17 : 0 3-OH and summed feature 3 (C16 : 1  ω 7 c and/or C16 : 1  ω 6 c ), and those of strain SC2-2 T were iso-C15 : 0 and anteiso-C15 : 0 . On the basis of the results of phenotypic and phylogenetic analyses, strains ADR-1 T and SC2-2 T represent two distinct novel species in the genus Chryseobacterium, for which the names Chryseobacterium oryzae sp. nov. (type strain ADR-1 T =KACC 19311 T =NBRC 113104 T ) and Chryseobacterium suipulveris sp. nov. (type strain SC2-2 T =KACC 19313 T =NBRC 113106 T ) are proposed.